Efficacy Of Vocal Cord Medialization by Injection Thyroplasty Using Liquid Paraffin In Relieving Hoarseness Of Voice In Idiopathic And Traumatic Unilateral Vocal Cord Paralysis - Saleem, Muhammad; Khan , Muhammad Sarim; Alamgir, Ashar; Rana, Muhammad Hamza; Hyder , Hafiz Sajjad; Ali, Syeda Jamila (Journal of Rawalpindi Medical College, 2024)
Objective: The objective of the study was to measure the efficacy of injection thyroplasty by liquid paraffin in the medialization of vocal cords in permanent post-traumatic or idiopathic hoarseness. Methodology: A total of 37 patients were enrolled in the study after obtaining approval from the ethical review board. The sample size was calculated using the WHO sample size calculator. All the patients in the study presented with hoarseness of voice due to either traumatic injury, idiopathic aetiology, or post-thyroidectomy. Samples were selected by simple random sampling. It was a Quasi-experimental study. All patients underwent an injection thyroplasty procedure using liquid paraffin to medialize the vocal cords. All the procedures were done under local anaesthesia. The patients were kept in follow-up for 1 year at an interval of 3 months. All the data was entered and analyzed by using SPSS version 24. Paired sample t-test was applied to measure pre-procedure and post-procedure scores. Results: The mean age of the participants was 38 years. Out of 37 patients 23 (62%) patients presented within 6 months of hoarseness of voice. 14 (38%) patients presented after 6 months of hoarseness of voice. 19 out of 23 patients (83%) underwent only a single dose of liquid paraffin via injection thyroplasty to resolve hoarseness of voice. However, out of 14 patients, 7 patients (50%) reportedly had to undergo 2 doses of liquid paraffin via injection thyroplasty. The p-value calculated was <0.005 which was statistically significant. Out of patients presenting after 6 months, 11 patients (79%) underwent transcervical phonation surgery. The p-value calculated was <0.05 which is statistically significant. Conclusion: Our study concludes that liquid paraffin is a safe and cost-effective solution for vocal cord paralysis. Liquid paraffin is not expensive and easily available which can be implied to yield excellent results to improve hoarseness of voice. Patients with late presentation are less likely to get the benefit of this procedure and may have to go for invasive transcervical phonation surgeries. It is recommended that this procedure should be done within 6 months of the development of hoarseness of voice. Keywords: vocal cord palsy, unilateral vocal cord paralysis, laryngeal paralysis, liquid paraffin, injection thyroplasty